2017
DOI: 10.1194/jlr.m072769
|View full text |Cite
|
Sign up to set email alerts
|

In vivo activation of leukocyte GPR120/FFAR4 by PUFAs has minimal impact on atherosclerosis in LDL receptor knockout mice

Abstract: and GPR120/FFAR4 that are activated by short-, medium-, or long-chain FAs (1-6). GPR120/FFAR4 is highly expressed in intestine, adrenals, lung, adipose tissue, and macrophages, and is described as the n-3 PUFA receptor (7). Upon activation by n-3 PUFA, GPR120/FFAR4 inhibits transforming growth factor -activated kinase 1 activation, resulting in attenuation of IKKB/NF-B and JNK/AP1 signaling (7). GPR120/FFAR4 expression regulates obesity in mice and humans; a nonsynonymous mutation (p.R270H) inhibited GPR120/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 55 publications
4
19
0
Order By: Relevance
“…Fish oil and borage oil were reported previously to reduce T.Ch, T.Gs and hepatic lipids in mice 44 which agreed with the current research. Oleic acid a monounsaturated fatty acid which is present as 20.163 and 12.771 in borage and fish oil, respectively were reported to have cardioprotective effect via improving vascular endothelial function 45 .…”
Section: Discussionsupporting
confidence: 93%
“…Fish oil and borage oil were reported previously to reduce T.Ch, T.Gs and hepatic lipids in mice 44 which agreed with the current research. Oleic acid a monounsaturated fatty acid which is present as 20.163 and 12.771 in borage and fish oil, respectively were reported to have cardioprotective effect via improving vascular endothelial function 45 .…”
Section: Discussionsupporting
confidence: 93%
“…We have demonstrated that botanical oils enriched in 18-carbon FAs beyond D6D [echium oil (EO), containing 18:4 n-3, and borage oil (BO), containing 18:3 n-6] result in efficient conversion and enrichment of their respective ≥20-carbon PUFAs, 20:5 n-3 and 20:4 n-6. Furthermore, compared with the saturated/monounsaturated FA-enriched palm oil (PO), dietary enrichment with EO or BO reduced plasma cholesterol concentrations, splenic monocytosis, neutrophilia, monocyte trafficking into aortic plaques, and atherosclerosis, similar to results observed with FO consumption ( 22 24 ).…”
mentioning
confidence: 58%
“…At 8 weeks of age, mice were randomly assigned to one of four groups consuming atherogenic diets containing 10% calories as PO and 0.2% cholesterol, supplemented with an additional 10% of calories as 1 ) PO, 2 ) BO (18:3 n-6 enriched), 3 ) EO (18:4 n-3 enriched), or 4 ) FO (20:5 n-3 and 22:6 n-3 enriched) for an additional 8–16 weeks. We also performed bone marrow transplantation as previously described ( 24 ). Briefly, bone marrow cells were harvested from cleaned femurs and tibias of male WT and atg5 MSKO mice and injected into irradiated (900 rads) Ldlr −/− mice (stock 002207) (7 × 10 6 bone marrow cells per mouse).…”
Section: Methodsmentioning
confidence: 99%
“…Notably, the in vivo significance of GPR120/FFA4 to suppress chronic low‐grade inflammation also has lately been contended. While GPR120/FFA4 activation by ω3‐PUFAs was initially reported to be critical to reduce high‐fat diet‐induced adipose tissue inflammation, more recent studies found GPR120/FFA4 to be dispensable for the therapeutic effects of ω3‐PUFAs in mouse models of both high‐fat diet‐induced adipose tissue inflammation, and of atherosclerosis . The reason for these discrepant findings is unknown and numerous explanations are conceivable.…”
Section: Discussionmentioning
confidence: 99%
“…While GPR120/FFA4 activation by ω3-PUFAs was initially reported to be critical to reduce high-fat diet-induced adipose tissue inflammation, 14 more recent studies found GPR120/FFA4 to be dispensable for the therapeutic effects of ω3-PUFAs in mouse models of both high-fat diet-induced adipose tissue inflammation, and of atherosclerosis. 35,36 The reason for these discrepant findings is unknown and numerous explanations are conceivable. Inflammation is a most complex process and ω3-PUFAs can exert diverse pharmacological actions independent of GPR120/FFA4.…”
Section: Discussionmentioning
confidence: 99%